Ironija Tomasa Kinga literārajos darbos - Karapetjana, Aikanuša (Latvijas Universitāte, 2008)
The bachelor paper Irony in Thomas King’s Writing is devoted to the research of irony in the collection of stories One Good Story That One. According to the author, T. King’s stories, representing the Canadian native literature serve as an example of irony reflecting the instances of interaction between two traditional within the context of the postmodern situation: the culture of Canadian natives representing the mythological world vision of the tribal period and the Christian, European-centred, white colonizers’ culture stemming out of the patriarchal culture. After the study of theoretical literature (chapters I and II), the author of the paper has analysed the functions of irony in each story (chapter III) The author of the paper concludes that, the most important function is to serve as a means for psychological self-protection. Keywords: Thomas King; Native Canadian literature; distancing, self-protecting, aggregative functions of irony

Bakalaura darbs „Ironija Tomasa Kinga darbos” veltīts ironijas pētījumam stāstu krājumā „Viens labs stāsts, tas stāsts”. Atbilstoši autores uzskatiem, T. Kinga stāstos pārstāvētā Kanādas indiāņu literatūra kalpo kā piemērs ironijai, kas atklājas, postmodernajā situācijā, saskaroties divām perspektīvām: Kanādas indiāņu kultūrai, kas pārstāv mednieku un vācēju cilšu mitoloģisko pasaules uzskatu, un kristīgajai, Eirocentriskajai balto kolonistu kultūrai, kura veidojusies patriarhālo uzskatu rezultātā. Pēc teorētiskās literatūras izpētes (I un II nodaļa), autore analizējusi ironijas pielietojumu katrā T. Kinga stāstā atsevišķi, apkopojot secinājumus, no kuriem galvenais: ironija kalpo kā psiholoģiskās pašaizsardzības līdzeklis. Atslēgvārdi: Tomass Kings; Kanādas indiāņu literatūra; distancējošā, pašaizsardzības, agregatīvā ironijas funkcija
Irony in Thomas King's Writing
Keywords: Filoloģija